The Effect of Antibiotics on Planktonic Cells and Biofilm Formation Ability of Collected Arcobacter-like Strains and Strains Isolated within the Czech Republic - Karolína Švarcová; Marcela Pejchalová; David Šilha (MDPI AG, 2022)
The purpose of this study was to test the in vitro effects of ampicillin, ciprofloxacin, clindamycin, erythromycin, gentamicin, and tetracycline on planktonic cells of Arcobacter-like microorganisms and on their biofilm formation ability. The minimum inhibitory concentrations (MICs) were determined by the microdilution method. Further, biofilm formation ability in the presence of various concentrations of antibiotics was evaluated by a modified Christensen method. Most of the 60 strains exhibited high susceptibility to gentamicin (98.3%), ciprofloxacin (95.0%), and erythromycin (100.0%). High level of resistance was observed to clindamycin and tetracycline with MIC50 and MIC90 in range of 4-32 mg/L and 32-128 mg/L, respectively. Combined resistance to both clindamycin and tetracycline was found in 38.3% of tested strains. In general, higher biofilm formation was observed especially at lower concentrations of antibiotics (0.13-2 mg/L). However, a significant decrease in biofilm formation ability of Pseudarcobacter defluvii LMG 25694 was exhibited with ampicillin and clindamycin at concentrations above 32 or 8 mg/L, respectively. Biofilm formation represents a potential danger of infection and also a risk to human health, in particular due to antimicrobial-resistant strains and the ability to form a biofilm structure at a concentration that is approximately the MIC determined for planktonic cells.